Cross-cultural healthcare communication system - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
In the previous chapter, how PPAC ontology is developed is presented. It shows all concepts, properties, and instances along with some case studies to understand the ontology use. In this chapter, we present healthcare communications systems in which the PPAC ontology and knowledge base place in as main components.